A neurolinguistic study of South Swedish word accents: Electrical brain potentials in nouns and verbs. Issue 2 (18th September 2015) - Roll, Mikael
Abstract : The brain response to words with correct and incorrect word accent–suffix combinations in South Swedish was investigated using electroencephalography (EEG). Accent 1 yielded an increased brain response ('preactivation negativity') that has previously been interpreted as reflecting preactivation of suffixes. Preactivation is greater for accent 1 due to its association with a limited set of suffixes, whereas accent 2 is default for compound words. The tonal realization of the word accent opposition in South Swedish is practically the mirror image of that in Central Swedish, where a similar preactivation negativity has been found. Therefore, the brain response is unlikely to result from a difference in acoustic features between the word accents. Invalidly cued suffixes yielded brain response pattern showing increased processing load of the unexpected suffix (negative electric potential) followed by its reprocessing (positivity 'P600').